2016
DOI: 10.1007/s00125-015-3850-y
|View full text |Cite
|
Sign up to set email alerts
|

Muscle sphingolipids during rest and exercise: a C18:0 signature for insulin resistance in humans

Abstract: Aims/hypotheses Ceramides and other sphingolipids comprise a family of lipid molecules that accumulate in skeletal muscle and promote insulin resistance. Chronic endurance exercise training decreases muscle ceramides and other sphingolipids, but less is known about the effects of a single bout of exercise. Methods We measured basal relationships and the effect of acute exercise (1.5 h at 50% V ⋅ O 2max ) and recovery on muscle sphingolipid content in obese volunteers, endurance trained athletes and individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
114
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(134 citation statements)
references
References 49 publications
17
114
2
1
Order By: Relevance
“…The same study also demonstrated that there was a positive correlation between plasma and muscle concentrations of Cer(d18:1/18:0), and this lipid correlated positively with visceral and liver fat and inversely with metabolic flexibility, which was determined by the change in respiratory quotient at rest and after insulin stimulation [24]. Another study supports these findings by showing that the concentration of Cer(d18:1/18:0) was significantly higher in type 2 diabetic individuals than athletes, and it was positively associated with BMI and inversely associated with insulin sensitivity [25]. However, there is a study demonstrating that Cer(d18:1/16:0) is more strongly increased than Cer(d18:1/ 18:0) in the muscle of obese individuals [26].…”
Section: Discussionsupporting
confidence: 75%
“…The same study also demonstrated that there was a positive correlation between plasma and muscle concentrations of Cer(d18:1/18:0), and this lipid correlated positively with visceral and liver fat and inversely with metabolic flexibility, which was determined by the change in respiratory quotient at rest and after insulin stimulation [24]. Another study supports these findings by showing that the concentration of Cer(d18:1/18:0) was significantly higher in type 2 diabetic individuals than athletes, and it was positively associated with BMI and inversely associated with insulin sensitivity [25]. However, there is a study demonstrating that Cer(d18:1/16:0) is more strongly increased than Cer(d18:1/ 18:0) in the muscle of obese individuals [26].…”
Section: Discussionsupporting
confidence: 75%
“…In fact, obese persons frequently have lower aerobic capacity and mitochondrial dysfunction and the cause of such dysfunction is less than clear. Moreover, a recent study, including obese volunteers, endurance‐trained athletes, and individuals with type 2 diabetes, found that muscle ceramide concentration increased during acute exercise and then decreased after the recovery to levels significantly lower than their baseline values, and the authors suggested that the change in muscle ceramides may promote insulin‐sensitizing effects of acute exercise (Bergman et al ., 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Only C18:0-Cer and C18:1-Cer species were elevated whereas C16:0-Cer remained stable. Recent studies link C16:0-Cer with hepatic insulin resistance [49,50] whereas skeletal muscle C18-derived ceramides account for majority of Cer accumulation in HFD animals [51], mice with uncontrolled STZ-diabetes [52] and in obese, diabetic patients [53]. Inhibition of de novo sphingolipid synthesis by myriocin also had greatest impact on C18:0-and C18:1-Cer species and was accompanied by significant improvement in both the whole-body and skeletal muscle insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%